In vitro anthelmintic activity of Chenopodium album and in-silico prediction of mechanistic role on Eisenia foetida. Issue 1 (January 2021) - Choudhary, Neeraj; Khatik, Gopal L.; Choudhary, Sunanda; Singh, Gurpal; Suttee, Ashish
Abstract: Helminths born diseases are related to pitiable management practices and improper control strategies. The medicinal plants contain various phytoconstituents that are liable for their anthelmintic activity. The aerial parts of the Chenopodium album were successively extracted with microwaves assisted extraction using petroleum ether, ethyl acetate, methanol, hydroalcoholic and aqueous solvents to get respective extracts (CAPE, CAEE, CAME, CAHE, and CAAE). All the extracts were analyzed for preliminary phytochemical screening for the identification of phytoconstituents. The anthelmintic activity was analyzed on Indian adult earthworms Eisenia foetida using piperazine citrate (PCT) as a standard drug. All the extracts (apart from CAAE) lead to paralysis and fatality of the earthworms. CAEE extract exhibits highly significant anthelmintic activity at a 10 mg/ml concentration by causing paralysis and fatality of earthworms and was more potent than PCT suspension. At a concentration of 10 mg/ml, paralysis and death time for CAEE was recorded as (10.08 ± 1.11) and (65.28 ± 2.09) respectively, while for standard piperazine citrate, it was recorded as (22.96 ± 1.12) and (65.09 ± 1.23). The CAEE exhibits two major compounds by LC-MS, i.e., NG and DG, that are mainly accountable for the Chenopodium album anthelmintic activity . The plant possesses GABA-mimetic action and thereby leads to flaccid, reversible paralysis of the body wall muscle. Abstract : Chenopodium album, Eisenia foetida, Piperazine citrate, Anthelmintic activity, LC-MS